Practical Reporting with Ruby and Rails - Berube, David (Apress, 2012)
This book is about general and scalable ways to create reports with Ruby. It covers using a huge array of tools—Rails, Gruff, Ghostscript, and many more—but a common thread links them all: they are powerful tools that will serve you even if you have a huge amount of data. Using the reporting tools and techniques described in this book, you will be able to solve almost any reporting problem, from small to very, very large. This book assumes you have some knowledge of Ruby and Rails, as well as access to a machine with Ruby, RubyGems, Rails, and MySQL installed. If you need to learn more about Ruby, I recommend reading Beginning Ruby: From Novice to Professional by Peter Cooper (Apress, 2007).2